Optimal Growth when Environmental Quality is a Research Asset - Christian Groth; Francesco Ricci (University of Copenhagen, Economic Policy Research Unit (EPRU), 2009)
If environmental quality positively affects the productivity of labor in R&D and pollution is caused by the use of a non-renewable resource, it is socially optimal to postpone extraction and to intertemporally adjust R&D effort.
Keywords: 330; endogenous growth; non-renewable resources; environmental quality; Neue Wachstumstheorie; Erschöpfbare Ressourcen; Umweltbelastung; Umweltbewertung; Theorie